PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PERUSAHAAN EKSPEDISI DI KOTA PEKANBARU - Lamin, Lamin (Eko dan Bisnis: Riau Economic and Business Review, 2021)
Abstract : This study aims to determine the effect of reward and punishment on the performance of shipping company employees in the city of Pekanbaru. In this study, data were collected through questionnaires to 100 people. The data analysis technique used is multiple regression analysis which serves to prove the research hypothesis. Based on the results, the t_count value of the reward variable is 3.584 while the t_table value is 1.984. it can be concluded that the reward has a significant effect on the performance of shipping company employees in the city of Pekanbaru. Based on the table above, the t_count value for the punishment variable is 2,655 while the t_table value is 1,984. it can be concluded that the punishment variable has a significant effect on the performance of shipping company employees in the city of Pekanbaru. The result of Adjuster R Square is 0.368 or 36.80%, which means that the magnitude of the effect of reward and punishment on employee performance is 36.80%.